Interventions to Promote Executive Development in Children and Adolescents - Elmoujahid, Oumaima (Journal of Educational and Psychological Sciences, 2025)
Executive functions develop naturally in typically developing individuals across different stages of life, from childhood to adulthood, with the aim of preparing them to adapt for the cognitive demands of subsequent developmental stages. The process of developing these skills varies from one individual to another, depending on several factors such as environmental contexts or adaptive dimensions, which may either facilitate or impede skills acquisition. Thus, enhancing executive skills is essential in the various stages of the individual. Therefore, we focused in this article on the childhood and adolescence stage with the aim of knowing how to effectively enhance these skills to facilitate the adaptation of the child and adolescent to the requirements of daily life on one hand, and with the evolution of the level of demand that increases with later stages, especially since adulthood is characterized by more complex challenges than the previous stages. In this article, which is a translation and a deep reading of a book chapter about executive functions (Dawson & Guare, 2014), a wide range of evidence-based intervention strategies that can be applied in different settings and age groups will be discussed, beginning with definitions of executive functions and identifying the different categories of skills categorized by researchers, as well as common issues in children and adolescents and their corresponding deficits in specific executive skills. Then, Guidelines will be provided to help identify appropriate intervention design, and how to choose the appropriate strategy to help children and adolescents develop their executive skills, whether at school or at home.
Keywords: Executive Skills; Executive Functioning; Executive Development; Guiding Principles; Intervention strategies